2020
DOI: 10.1007/s10800-020-01408-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water on the electrodeposition of copper from a deep eutectic solvent

Abstract: This study has examined the effect of water on the electrodeposition of copper from a deep eutectic solvent (DES). Initial physiochemical measurements showed that the viscosity and resistivity of the DES decreased with added water in the range 1 -15 wt%. This reduction in viscosity resulted in an increase in the mass transfer limiting current, without narrowing the electrochemical window or altering the speciation of the copper chloro-complexes. This shows that metal deposition rates can be increased by water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 52 publications
(135 reference statements)
1
43
0
Order By: Relevance
“…On the other side, Cu deposition in 1:2 ChCl/EG is positively affected by water. Valverde et al 56 demonstrated that water increases deposition rates and electrolyte conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…On the other side, Cu deposition in 1:2 ChCl/EG is positively affected by water. Valverde et al 56 demonstrated that water increases deposition rates and electrolyte conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…In the present case, the double layer charging is controlled by the kinetically slow second step: CuCl2 -+ e- Cu + 2Cl -. In a previous study 22 values of c = 0.42 and i0 = 5.7 mA cm -2 were determined for this for this reaction. Using these values and a measured double layer capacitance of Cdl = 15 F cm -2 , the charge and discharge times were estimated.…”
Section: Selection Of Pulse Parameters For Electrodepositionmentioning
confidence: 99%
“…[32][33][34] Even if the presence of water does not appear to lead to the electrolyte decomposition, the residual water included in the DES structure should be considered, as it affects -mostly beneficially -electrodeposition, 35,36 may reduce the electrochemical potential window, alter speciation and in general complicate the reproducible performance of measurements. [37][38][39] An interesting work reported an atomic force microscope study of the interfacial nanostructure of three ChCl-based DESs (U, G, or ethylene glycol EG as HBD) at a platinum (Pt) electrode as a function of applied potential and water content. 40 Results revealed that the interfacial nanostructure increases upon addition of water up to ~40 wt%, after which it decreases.…”
Section: Typementioning
confidence: 99%
“…Despite the above mentioned donwsides, DESs have been used in many electrochemical processes, 28 including metal oxide processing, 25,43,44 electropolishing, [45][46][47][48][49] and electrodeposition of metals and alloys. 16,35,36,38,39, DESs have been electrochemically characterized using redox couples such as ferrocene, 24,76 iron (III) acetylacetonate, 77 copper(II)/copper(I), 41 and other metallic ions. [78][79][80][81] Also, the electrochemistry and adsorption behavior at the interface DES-electrodes has been investigated.…”
Section: Typementioning
confidence: 99%